198 Primary care use of SGLT2 inhibitors in patients with type 2 diabetes mellitus and cardiovascular disease – are we missing a trick?. (4th June 2021) - Higson, David; Turley, Andrew
Abstract : Background: Patients with Type 2 Diabetes Mellitus (T2DM) and Atherosclerotic Cardiovascular Disease (ASCVD) have an average reduction of 12 years in life expectancy. The landmark EMPA-REG trial in 2013 demonstrated that SGLT2i significantly reduced risk of all-cause mortality in this population of patients. The NNT was 39 at 3.1 years. This is comparable to other landmark studies such as the 4S study (Simvastatin NNT 30 at 5.3 years) and the HOPE trial (Ramipril, NNT 50 at 5 years). International guidelines recognise the CV benefits of SGLT2i. They suggest SGLT2i should be used as a second line therapy or as a first line intervention in treatment naïve T2DM patients who have ASCVD. Objectives: To assess use of SGLT2i in patients with T2DM and known ASCVD in primary care. Additionally, to understand the potential benefit of introducing SGLT2i to these patients in primary care. Methods: The patient list of a GP surgery was searched for patients coded to have T2DM and ASCVD. Demographics, most recent HbA1c and eGFR, diabetic and cardiology medication were recorded. Search criteria were as follows: Myocardial Infarction, Unstable Angina, Ischaemic Stroke, Haemorrhagic Stroke, Peripheral Artery Disease, AAA, Coronary Artery Bypass Graft, Percutaneous Coronary Intervention, Percutaneous Transluminal Coronary Angioplasty. Results: 8525 patients registered, 487 had T2DM (5.7%) and 68 patients were identified as having T2DM and ASCVD. 5 were excluded from analysis, one patient had left the surgery, three had no coronary atheroma on angiogram and one was mis-coded. Therefore 63 patients were used for analysis (12.9% of those with T2DM). Mean age 77.2 (SD 10.13), 41 male and 22 female. 58 patients had an eGFR >30, 29 patients had an eGFR >60. 45 patients were receiving at least one medication for T2DM (table 1). 18% of patients taking medication were receiving either GLP-1 or SGLT2i which confer CV benefit ( figure 1 ). 75% of patients on dual therapy were taking DPP-4 inhibitors compared with 6.25% patients who were taking SGLT2i. DPP-4 inhibitors have no CV benefit. SGLT2i were typically used as a third line or later therapy ( figure 2 ). Conclusion: SGLT2i were used sparingly and typically as a third line therapy or later in this cohort. DPP-4 inhibitors tended to be used as second line but lack any CV benefits. With a NNT of 39, concerted efforts to increase SGLT2i use in patients with T2DM and ASCVD have the potential to be an effective intervention in primary care that ultimately saves lives. Conflict of Interest: None